GCG, CSR and Interest Rate as Determinant of Firm Value - Amellia Pragita; Naelati Tubastuvi; Wida Purwidianti; Arini Hidayah (Jurnal Proaksi, 2026)
Main Objectives - This study examines the influence of GCG, CSR, and interest rates on the value of companies in the Indonesian financial sector during the period 2021–2024.Method - This study uses a quantitative approach with secondary data that there are 25 financial companies that meet the criteria from 105 companies listed on the IDX, analyzed through panel data regression using Stata 17 MP.Key Findings - The results of the study show that managerial ownership significantly increases the value of the firm , while the board of directors, independent commissioners, CSR, and interest rates have no effect. This shows that managerial ownership is crucial in increasing the value of companies in the financial sector.Theoretical and Practical Implications - Theoretically, the results of this study support agency theory and arbitrage theory, which show that managerial ownership aligns the interests of management and shareholders, while market efficiency affects the value of the firm . Practically, companies must strengthen the implementation of GCG and CSR to increase firm  value.Novelty -  This study extends prior research by adding managerial ownership and interest rates to the analysis of firm value. It also shifts the context to the Indonesian financial sector during the 2021–2024 period.